2017
DOI: 10.1136/bjophthalmol-2016-309481
|View full text |Cite
|
Sign up to set email alerts
|

Choroid morphometric analysis in non-neovascular age-related macular degeneration by means of optical coherence tomography angiography

Abstract: Patients with non-neovascular AMD show significant choroidal vascular depletion and fibrotic replacement, suggesting a possible role in the pathogenesis and progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 34 publications
4
51
1
Order By: Relevance
“…Additionally, the percentage of nonperfused CC on OCTA correlated with visual acuity in RPD eyes. Similar results were reported by Cicinelli et al [41] by means of binarized OCTA scans. Chatziralli et al [42] additionally observed that one-third of patients with RPD also revealed CC flow impairment in areas outside of RPD affection.…”
Section: Octa In Dry Amdsupporting
confidence: 81%
“…Additionally, the percentage of nonperfused CC on OCTA correlated with visual acuity in RPD eyes. Similar results were reported by Cicinelli et al [41] by means of binarized OCTA scans. Chatziralli et al [42] additionally observed that one-third of patients with RPD also revealed CC flow impairment in areas outside of RPD affection.…”
Section: Octa In Dry Amdsupporting
confidence: 81%
“…OCT‐A has been extensively used in both non‐neovascular and exudative age‐related macular degeneration. In non‐neovascular age‐related macular degeneration, an increase in choriocapillaris flow voids was observed with increasing numbers of drusen and reticular pseudodrusen . In keeping with histology samples, pronounced choriocapillaris flow impairment is seen below geographic atrophy lesions .…”
Section: Applications In Retinal Diseasesupporting
confidence: 63%
“…Cicinelli et al. () used OCT‐A to evaluate CC vascular density on binarized images in patients with drusen and RPD reporting decreased density in comparison with healthy controls. Chatziralli et al.…”
Section: Discussionmentioning
confidence: 99%